A study of the production system of Progressive Laboratories, Inc. - Falcis, Charlene Therese M.; Ricalde, Rebecca R.; Varona, Andrew James P. (Diliman, Quezon City College of Engineering, 2002)
Progressive Laboratories Inc., is a toll manufacturing company that produces premixes liquid injectibles and vitamin tables. The focus of the study is on the five products that compose the vitamin tablets group: Vermigo, Baxidil, Cosumix, Pakyaw and Dynamutilin. These tablets undergo most of the manufacturing processes available to the company, manufactured constantly throughout the year and represent a relatively large production and market share. Three problems are identified: stockout of packaging materials, scheduling difficulties and occurrence of bottlenecks. The general plan of solution starts with forecasting the demand for the next five years. The results are then used in establishing an inventory system for the packaging materials warehouse and in developing a yearly production schedule for the tablet line. Capacity analysis is done on the machines to identify the bottleneck, and the plant layout is also studied to trace the flow of materials around the plant. Recommendations include establishing a forecasting technique using the Multiplicative Seasonal Method and a fixed order quantity (Q) inventory system for the packaging materials warehouse. The forecasted demands for the year should be leveled in order for the company to develop a yearly production schedule and avoid erratically changing production rates. For the blister packaging process, found out to be the bottleneck, it is suggested that two additional workers be hired. If possible, in the long run, Progressive Laboratories should also purchase another blister-packing machine. Lastly, the plant layout is modified to have a more organized materials flow. Implementation plans for the major recommendations are provided for better understanding. Minor recommendations are shifting from a process layout to a hybrid layout and application of methods engineering to the company's manual processes.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Progressive Laboratories Incorporated; Pharmaceutical industry; Production engineering